2016
DOI: 10.1007/s11695-016-2352-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Ability of Clinical Scores to Predict Obstructive Sleep Apnea (OSA) Severity in Susceptible Surgical Patients

Abstract: ClinicalTrial.gov NCT02051829.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…In the surgical population, two of six studies reported data at multiple cut-off points for the STOP-Bang questionnaire for moderate-to-severe OSA (AHI ≥ 15) [ 62 , 63 ]. Increasing the threshold from 4 to 7 increased specificity from 31% (95% CI: 0.2, 0.4) to 96% (95% CI: 0.89, 0.99) and was greatest at cut-off values ≥ 6 and ≥ 7 (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the surgical population, two of six studies reported data at multiple cut-off points for the STOP-Bang questionnaire for moderate-to-severe OSA (AHI ≥ 15) [ 62 , 63 ]. Increasing the threshold from 4 to 7 increased specificity from 31% (95% CI: 0.2, 0.4) to 96% (95% CI: 0.89, 0.99) and was greatest at cut-off values ≥ 6 and ≥ 7 (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Рівень тривожності та депресії оцінювався вранці після першої після операційної ночі з використанням госпіталь-ної шкали тривоги та депресії (HADS) [14,15]. Ризик обструктивного сонного апное оцінювався за шкалою DES-OSA [16]. Також проводилась оцінка анестезіологічного ризику за ASA, тривалості оперативного втручання, очікуваного рівня болю та споживання ненаркотичних та наркотичних анальгетиків [17].…”
Section: матеріали та методиunclassified
“…Several predictive scores have been proposed and validated to detect OSA patients preoperatively. The four scores most often used in anesthesia are the STOP-Bang, the P-SAP, the OSA50, and the DES-OSA scores [ 22 27 ]. These scores are illustrated in Fig 1 .…”
Section: Introductionmentioning
confidence: 99%